PROSPEK PEMANFAATAN BAHAN BAKAR BATUBARA CAIR (BBBC) UNTUK MENDUKUNG DIVERSIFIKASI ENERGI - Rahardjo, Irawan (Badan Pengkajian dan Penerapan Teknologi, 2008)
A study of energy diversification in Indonesia and the how role of coalliquefaction if implemented w conducted. Liquified brown coal fuel (LBCF) is apotential alternative energy for substituting crude oil, which is processed toproduce synthetic fuel from coal. In addition, the government policy on reducingoil dependency makes the liquified brown coal fuel an option which must berealized soon. This paper reveals that LBCF is very prospective in order tosupport energy diversification program. In 2014 LBCF from Berau plant wouldsubstitute Balikpapan oil refinery throughput as much as 20% or about 57.99 PJ.It increases to 42.5% or 173.96 PJ in 2020. LPG produced as side product ofliquefaction plant could be used to support LPG supplied by LPG plant Aral andBadak and Balikpapan oil refinery. The amount of the substitution is increasingup to 56% in 2018, or at a rate of 19.52% per year.Kata kunci: coal liquefaction, diversification, liquid petroleum gas